(untitled) (Journal of the College of Basic Education, 2024)
The Banu Marin played an important role in the history of Al-Aqsa Morocco, and their reign witnessed prosperity and strength at its beginning, but after the killing of Sultan Abu Anan Faris Al-Marini (749-759 AH / 1348-1358 AD), a major shift occurred in the political system of the state, as actual power was transferred from the hands of the sultans. Young people who lacked experience in ruling, were placed in the hands of their ministers who took themselves as guardians over them. These sultans, who were hidden under the guardianship of their ministers, had a negative impact on the state, which led to the deterioration of its conditions in all political, economic and social aspects, as well as the interference of the Jews in its affairs, and they controlled the reins. The state, and corruption began to spread in the body of the Marinid state, and this angered the people, which prompted them not to submit to this violence, and they launched a revolution, as a result of which the Marinid state ended, and its last sultan, Abd al-Haqq bin Abi Saeed Othman II (d. 869 AH / 1464 AD), was killed, and its eventual fall.